A temática étnico-racial no ensino superior: Estudo de caso do acervo das bibliotecas UFU - Rodrigues, Viviane Fonseca (2023)
The present work proposes a case study based on the survey of the racial theme in Higher Education, in the context of the libraries of the Federal University of Uberlândia (UFU), referenced by the normative legal framework of the current affirmative actions in force in higher education, among which we highlight Law no. 10,639 (BRASIL, 2003). In this path, we emphasize the importance of Education for Ethnic-racial Relations (ERER, in Portuguese abbreviation) and the development of effective actions that allow its understanding, mainly with regard to higher education, the focus of this research. This study also exposes a reflection on the implementation of that law at UFU, in which the affirmative actions carried out by the institution for this purpose stand out. In this context, it presents the role of university libraries as disseminators of knowledge and academic scientific production, as well as the relevance of their bibliographic collection as supporting tools for studies that address racial issues. As a methodological proposal, in addition to the literature review, there was a bibliographic survey of the physical and digital collection of the UFU Library System (SISBI) on the theme of ethnic-racial relations and Afro-Brazilian and indigenous culture, with the aim of demonstrating, through a quantitative and qualitative analysis of charts and graphs, the existing works in this collection and the production of academic works related to the theme, as well as the importance of the works for the community. In carrying out the study, we opted for a research focused on the platforms of physical and digital works present on the institution's website. Finally, we understand that the bibliographical survey explained in this investigation demonstrated, according to the quantitative and qualitative analyzes carried out, that Sisbi’s physical and digital collection has works that stand out in terms of ethnic-racial relations, which can help the research of academics and researchers on the subject; however, specifically in the Sectoral Library of Campus Umuarama (BSUMU), there is a certain deficiency of these works in physical format, due to the lack of requests from users in relation to this demand. This leads us to infer that Digital Information and Communication Technologies (TDICs) tend to replace the physical collection or that the undergraduate courses on the aforementioned Campus may not include the racial theme in their disciplines or pedagogical practices. We noticed that, although the UFU has carried out several affirmative actions with a view to racial equality in the academic field, the ERER has been implemented in a slow and ineffective way in the university's teaching plans, which does not contribute to a student formation of more aware citizens, critical and democratic. Therefore, there is still a long way to go before the implementation of Law n. 10.639/2003 effectively in the academic environment.